Drawing down the moon : magic in the ancient Greco-Roman world - Edmonds, Radcliffe G., III, 1970- (Princeton University Press, 2019)
What did magic mean to the people of ancient Greece and Rome? How did Greeks and Romans not only imagine what magic could do, but also use it to try to influence the world around them? In Drawing Down the Moon, Radcliffe Edmonds, one of the foremost experts on magic, religion, and the occult in the ancient world, provides the most comprehensive account of the varieties of phenomena labeled as magic in classical antiquity. Exploring why certain practices, images, and ideas were labeled as "magic" and set apart from "normal" kinds of practices, Edmonds gives insight into the shifting ideas of religion and the divine in the ancient past and in the later Western tradition. Using fresh approaches to the history of religions and the social contexts in which magic was exercised, Edmonds delves into the archaeological record and classical literary traditions to examine images of witches, ghosts, and demons as well as the fantastic powers of metamorphosis, erotic attraction, and reversals of nature, such as the famous trick of drawing down the moon. From prayer and divination to astrology and alchemy, Edmonds journeys through all manner of ancient magical rituals and paraphernalia--ancient tablets, spell books, bindings and curses, love charms and healing potions, and amulets and talismans. He considers the ways in which the Greco-Roman discourse of magic was formed amid the cultures of the ancient Mediterranean, including Egypt and the Near East. An investigation of the mystical and marvelous, Drawing Down the Moon offers an unparalleled record of the origins, nature, and functions of ancient magic